Contraceptive practices and induced abortions status among internal migrant women in Guangzhou, China: a cross-sectional study - Zeng, Jiazhi (BMC Public Health, 2015)
BACKGROUND: China is facing the unprecedented challenges of internal migration. Migrants tend to have poorer utilization of health and family planning services as compared to the local residents. Migrant women are at greater risk of induced abortions due to their poor contraceptive knowledge and attitude. This study aims to understand the contraceptive practices and history of induced abortions, explore the potential factors influencing induced abortions, and evaluate the utilization of family planning services among migrant women in Guangzhou, China. METHODS: An anonymous, self-administered questionnaire survey was conducted with 1003 migrant women aged 18–49 in Guangzhou, China in 2013. A multi-stage sampling method was employed. Binary logistic regression model was used for analyzing risk factors of induced abortions. RESULTS: Among the 1003 participants, 810 (80.8 %) reported having sex in the past 6 months, including 715 (88.3 %) married and 95 (11.7 %) unmarried. The most reported contraceptive method was male condom (44.9 %), while 8.1 % never used any contraceptive methods. Only 10.4 % reported having attained free condoms from family planning service stations (FPSSs) and 39.3 % reported having acquired contraceptive knowledge from family planning workers. Of all the participants, 417 (41.6 %) had a history of induced abortion. Of married and unmarried women, 389 (49.1 %) and 28 (14.0 %) had induced abortion respectively. Of these, 152 (36.5 %) had repeated abortions. The most reported reason for having induced abortion was failure of contraception (31.9 %), followed by nonuse of any contraceptives (21.1 %). Migrants who had induced abortion tended to be older, have household registration outside Guangdong province, receive no annual health checkup, have lower education, have urban household registration, have lived longer in Guangzhou and have children (P < 0.05). CONCLUSIONS: The prevalence rate of induced abortion, especially repeated abortions among migrant women was high in Guangzhou, China. There is an urgent need to improve the awareness of regular and appropriate use of contraceptives. The utilization of FPSSs among migrant women was reportedly low. Family planning system should be improved to provide better access for migrants and better integrated with the general health services. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-015-1903-2) contains supplementary material, which is available to authorized users.